Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention Guru - Daeli, Ivan Christian; Syahrial, Hery (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
The purpose of this research is to determine and analyze the influence of Job Satisfaction on turnover intention, to determine and analyze the influence of Organizational Commitment on turnover intention, to determine and analyze the influence of Job Satisfaction and Organizational Commitment on the turnover intention of teachers at SMP Negeri 3 Percut Sei Tuan partially. This research uses an associative type of research using a quantitative approach, which is carried out to analyze the relationship or influence between two or more variables. The population in this study was 70 teachers at SMP Negeri 3 Percut Sei Tuan with a sample of 54 people. The sample was selected through or using convenience sampling. Data obtained from a questionnaire using a Likert scale was distributed via Google Form to teachers at SMP Negeri 3 Percut Sei Tuan. Next, the data obtained was analyzed using SEM-PLS version 3.0. The results of the analysis show that there is a negative and significant influence between job satisfaction and turnover intention, with a value of -0.491 and a significance of 0.000 0.05.